CP-017 Reconfiguration to single bed wards: Quantification of the time impact on the ward based clinical pharmacy service. (14th February 2016) - Kieran, M; Meegan, C
Abstract : Background: The ward visit and individual patient review is a primary role of the ward-based Clinical Pharmacist. In 2012, clinical areas such as theatres, radiology and selected wards relocated to a new state of the art building. Relocation of wards involved a reconfiguration of the ward layout from a combination of multiple bedded rooms with some single bed rooms to an entirely single bedded configuration. New building wards occupy approximately twice the surface area of existing hospital wards. While the reconfiguration improves clinical efficiency, patient satisfaction and infection control, there had been little focus on resource utilisation. From a Pharmacy perspective, drug storage rooms and drug delivery locations increased on some wards, coupled with an increased surface area to walk. Purpose: To quantify the time impact of moving to a single bed ward configuration on the Clinical Pharmacist ward based service. Material and methods: Clinical Pharmacist ward visits were timed over a two week period on wards pre and post relocation to the Whitty Building. The results were analysed. Qualitative feedback from the clinical pharmacists on ward visit time differences was reviewed Results: 6 wards relocated to a single bed configuration. The average time to complete a Clinical Pharmacist ward visit on these wards increased by a total of 1.6 h per day, an average of 0.27 h per ward. The average time to complete a Clinical Pharmacist ward visit per bed increased with the relocation to single bedded wards on 5 out of the 6 wards. The average time to complete a Clinical Pharmacist ward visit per bed increased by 1 min per patient. Conclusion: Clinical Pharmacist ward visit timings increased with ward relocations to single bedded wards. Root causes analysis identified causative factors which include the ward surface area, an increase in drug storage locations, patient turnover and amendments to outpatient clinic locations References and/or Acknowledgements: Infection Prevention and Control Bulding Guidelines for Acute Hospitals in Ireland; A Strategy for the Control of Antimicrobial Resistance in Ireland (SARI), 2008, accessed via www.hspc.ie No conflict of interest.